Source-to-sink coupling and spatiotemporal evolution during multiphase rifting: The Jurassic-Cretaceous Lishu fault depression, Southeastern Songliao Basin - Ke Wang; Yong Zhou; Jingchi Yan; Yuejie Zhang (PLoS ONE, 2026)
Source-to-sink (S2S) systems exert a fundamental control on sediment dispersal and reservoir development in multiphase rift basins; however, their coupling mechanisms and spatiotemporal evolution remain poorly constrained. The Lishu Fault Depression, located in the southeastern Songliao Basin of Northeast Asia, represents a typical example of a multiphase rift lacustrine basin. Nevertheless, incomplete understanding of its S2S dynamics has hindered effective hydrocarbon exploration and development. In this study, sequence stratigraphy, sedimentology, and S2S system theory are integrated with seismic, drilling, and well-log data to construct a high-resolution sequence stratigraphic framework and to quantitatively characterize sediment provenance, transport pathways, and depositional systems. On this basis, paleo- S2S systems are reconstructed and systematically classified. The results indicate that seven sequence boundaries can be identified within the Jurassic-Cretaceous succession of the Lishu Fault Depression, delineating six third-order sequence stratigraphic units (SQ1-SQ6). Analysis of boundary fault activity reveals that the Sangshutai Fault exhibits higher displacement rates in its central segment and progressively weaker activity toward both ends, with peak fault activity occurring during the late stage of intense rifting. During this rifting phase, sediment supply was dominated by multiple provenance systems, while sediment-routing pathways primarily developed as fault-controlled valleys, structural transfer zones, and parallel fault-step zones. These pathways exerted a strong control on the spatial distribution of nearshore subaqueous fans, fan deltas, braided river deltas, and lacustrine deposits. From the early rifting stage through the rift atrophy stage, the basin evolved from a tectonic framework characterized by alternating uplifts and depressions into a unified lacustrine basin, and subsequently into a shallow, laterally extensive lake system. During the initial rifting stage, steep-slope nearshore subaqueous fans and slope–fan delta systems developed. In the early phase of intense rifting, dominant patterns included steep slope–transfer zone–fan delta, axial slope–fan delta, and eastern gentle slope parallel fault-step zone systems. In the late phase, axial drainage systems prevailed, forming axial slope–braided river delta patterns. During the late rifting stage, gentle slope–braided river delta source-to-sink systems became dominant. Quantitative analyses further demonstrate that, during the intense rifting stage, the scale of gravity-flow-dominated nearshore subaqueous fans and traction-current-dominated deltaic deposits is positively correlated with the width, depth, and cross-sectional area of sediment-routing valleys. These results elucidate the dynamic coupling between tectonic processes and S2S system evolution in multiphase rift basins, and provide a robust geological basis for predicting sand body distribution and guiding deep hydrocarbon exploration in the Lishu Fault Depression and analogous rift basin settings.